Breast Cancer Treatment and Survival Among Department of Defense Beneficiaries: An Analysis by Benefit Type and Care Source. Issue 3 (22nd January 2018) - Manjelievskaia, Janna; Brown, Derek; Shao, Stephanie; Hofmann, Keith; Shriver, Craig D; Zhu, Kangmin
Abstract: Background: Use of treatment for breast cancer is dependent on the patient's cancer characteristics and willingness to undergo treatment and provider treatment recommendations. Receipt of breast cancer treatment varies by insurance status and type. It is not clear whether different benefit types and care sources differ in breast cancer treatment and outcomes among Department of Defense beneficiaries. Methods: The objectives of this study are to assess whether receipt of breast cancer treatment varied by benefit type (TRICARE Prime vs non-Prime) or care source (direct care, purchased care, and both) and to examine whether survival and recurrence differed by benefit type and/or care source among female Department of Defense beneficiaries with the disease. Study subjects were women aged 40–64 yr, diagnosed with malignant breast cancer between 2003 and 2007. Multivariable logistic regression analyses were conducted to assess the likelihood of receiving treatment by benefit type or care source. Multivariable Cox proportional hazard models were used to investigate differences in survival and recurrence by benefit type or care source. Findings: A total of 2, 668 women were included in this study. Those with Prime were more likely to have chemotherapy, radiation, hormone therapy, breast-conserving surgery, surveillance mammography, and recurrence than women with non-Prime. Survival was high, with 94.86% of those with Prime and 92.58% with non-Prime alive at the end of the study period. Women aged 50–59 yr with non-Prime benefit type had better survival than women with Prime of the same age. No survival differences were seen by care source. In regard to recurrence, women aged 60–64 yr with TRICARE Prime were more likely to have recurrent breast cancer than women with non-Prime. Additionally, women aged 50–59 yr who used purchased care were less likely to have a recurrence than women who used direct care only. Discussion/Impact/Recommendations: To our knowledge, this is the first study to examine breast cancer treatment and survival by care source and benefit type in the Military Health System. In this equal access health care system, no differences in treatment, except mastectomy, by benefit type, were observed. There were no overall differences in survival, although patients with non-Prime tended to have better survival in the age group of 50–59 yr. In regard to care source, women who utilized mostly purchased care or utilized both direct and purchased care were more likely to receive certain types of treatment, such as chemotherapy and radiation, as compared with women who used direct care only. However, survival did not differ between different care sources. Future research is warranted to further investigate variations in breast cancer treatment and its survival gains by benefit type and care source among Department of Defense beneficiaries.